ANALISIS PRODUK PELEK MOTOR TIPE CAST WHEEL BERBAHAN PADUAN ALUMUNIUM - Chandra Teguh Trimulya (2020)
Motorcycle rim is a very important component in vehicles where motorcycle rim is a component that is directly confused with the highway. In the aspect of safety rim is also very important and very calculated in the manufacturing process, the use of high quality raw materials is very necessary in the manufacture of motorcycle rims. Nowadays, cast wheel rims are very popular among consumers because cast wheel rims have a more sporty design compared to spokes. In this research, the design of cast wheels with spoke wheels numbered 5 and 6 with a given impact speed variation of 10km/h, 15km/h and 20km/h. then the rim material used uses aluminum alloy 6061-T6 and the projectile material uses aluminum alloy 6061-T0. The rim that is designed has a diameter of 433.3 mm and a width of 68 mm to make it easier to design a cast wheel rim using software based on the finite element method, by using this software we can design or design a material so that we can know the stress and strain that occurs when simulating an impact on the inter-spoke plane.